Prediction of postspinal hypotension in elective caesarean section: An observational study - Kanchan Chauhan; Poornima N; Kshama Rao; Anuapama Nagar (Journal of Applied Pharmaceutical Research, 2023)
Objectives: Spinal anaesthesia is the most preferred method of anaesthesia for a caesarean section. The frequent complication of the subarachnoid block is hypotension. This study aimed to find out the association of pre-operative heart rate with post-spinal hypotension. Materials and Methods: A total of 100 pregnant patients, ASA physical status І and ІІ, aged between 20-35 years, undergoing elective caesarean section, under spinal anaesthesia. The patient’s baseline heart rate, Systolic blood pressure, Diastolic blood pressure, Mean arterial pressure, and SPO2 were noted. Incidence of hypotension and mephentermine requirement following spinal anaesthesia noted. Results: Fifty-seven out of 100 patients developed hypotension (57.0%) of whom 48 were in the subgroup with HR >90bpm (67.0%) and 09 patients were in the group with HR < 90bpm (31.0%). The baseline heart rate was statistically significant with a p-value of 0.001. The average dose of mephentermine required to correct hypotension was 9.47±4.8 mg. Conclusion: Baseline heart rate is a promising predictor of postspinal hypotension in obstetric patients undergoing elective caesarean section.